2016
DOI: 10.1016/j.autneu.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

GABA mechanisms of the nucleus of the solitary tract regulates the cardiovascular and sympathetic effects of moxonidine

Abstract: The antihypertensive drugs moxonidine and clonidine are α2-adrenoceptor and imidazoline (I1) agonists. Previous results from our laboratory have shown that moxonidine can act in the commissural nucleus of the solitary tract (commNTS). In addition, some studies have shown that GABA or glutamate receptor blockade in the RVLM blunted the hypotension produced by these antihypertensive agents in spontaneously hypertensive rats. Therefore, in the present study we verify whether the cardiovascular and sympathetic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recently, it has been suggested that the cardiovascular and sympathetic effects elicited by MOX are dependent on GABA receptors 31 . Injection of the GABA A receptor antagonist bicuculline into the commissural nucleus of the solitary tract reduced hypotension and sympathoinhibition induced by MOX 31 . MOX has also been demonstrated to alleviate RVLM oxidative stress and neuronal injury in diabetic rats 32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that the cardiovascular and sympathetic effects elicited by MOX are dependent on GABA receptors 31 . Injection of the GABA A receptor antagonist bicuculline into the commissural nucleus of the solitary tract reduced hypotension and sympathoinhibition induced by MOX 31 . MOX has also been demonstrated to alleviate RVLM oxidative stress and neuronal injury in diabetic rats 32 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other mechanisms should be also considered. Recently, it has been suggested that the cardiovascular and sympathetic effects elicited by MOX are dependent on GABA receptors 31 . Injection of the GABA A receptor antagonist bicuculline into the commissural nucleus of the solitary tract reduced hypotension and sympathoinhibition induced by MOX 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both sympathetic-controlled HRV and parasympathetic-controlled HRV were decreased in patients with right hemisphere stroke involving reduced bilateral insula volumes [30, 32]. Further, these patients were more susceptible to cardiac complications such as arrhythmias and sudden death due to autonomic imbalance [33, 34]. …”
Section: Interaction Between Cardiovascular Changes and Specific Bmentioning
confidence: 99%